Psychosocial predictors of active aging: Evidence in a sample of older adults - Blanco Molina, Mauricio (2011)
The study focused on the identification and analysis of the psychosocial factors that determine that older people living in Costa Rica keep active or successful lifestyles. The findings showed the importance of the phenomenon by analyzing the social, psychological and biophysical conditions, identifying the psychosocial, as the most successful to explain. The psychological variables were recognized as predictors and main determinants, particularly, self-efficacy and cognitive state, as well as a series of personal resources such as positive thinking, perseverance and adaptability, among others. This was explained in conjunction with the presence of variables such as adequate social support networks and socioeconomic stable trend to high levels of education, among others, for example, which allowed tobuild a consistent “portrait” of successful or active aging elderly people.